Alternatives to Animal Testing 2018
DOI: 10.1007/978-981-13-2447-5_6
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Eliminating One-Year Dog Studies for the Safety Assessment of Pesticides

Abstract: We reviewed six key peer-reviewed publications that assessed the need for one-year studies of pesticide toxicity in dogs. Each of the six papers took a different approach to comparing the value of one-year studies relative to three-month studies, and despite the adoption of different databases and approaches, each study reached the same conclusion: the recommended limit to the testing of pesticide toxicity in dogs should be three months. Therefore, the present review supports the conclusion that the routine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The globalization of industries sometimes creates opportunities but often hurdles (Bottini et al, 2007). An impressive example was the initiative to abandon the one-yeardog study for pesticides: Six major studies showed the limited usefulness of this test (Spielmann, 2019), resulting in changes to regulatory requirements that struck the study in the EU in 2009 and made it required in the US, Canada, and Australia only when dogs are shown to be more sensitive than rodents in 90-day studies. Still, this meant no change for agrochemical companies until most recently Brazil, Korea, and Japan took similar positions, following lobbying activities of several partners.…”
Section: Challengementioning
confidence: 99%
“…The globalization of industries sometimes creates opportunities but often hurdles (Bottini et al, 2007). An impressive example was the initiative to abandon the one-yeardog study for pesticides: Six major studies showed the limited usefulness of this test (Spielmann, 2019), resulting in changes to regulatory requirements that struck the study in the EU in 2009 and made it required in the US, Canada, and Australia only when dogs are shown to be more sensitive than rodents in 90-day studies. Still, this meant no change for agrochemical companies until most recently Brazil, Korea, and Japan took similar positions, following lobbying activities of several partners.…”
Section: Challengementioning
confidence: 99%
“…24 Only recently have OECD countries decided to make the one-year dog test a conditional requirement and necessary only on a case-by-case basis. 25 The rapid progress and advances in the sciences, agrochemical risk assessment and agricultural practice Figure 1. Techno-regulatory conceptual landscape map illustrating the various parts that need to be considered in a conceptual model.…”
Section: Optimizing Agrochemical Safetymentioning
confidence: 99%
“…Although the first evidence that this test was redundant emerged in the 1980s, 23 it was recognized by major regulatory authorities much later, in 2006 24 . Only recently have OECD countries decided to make the one‐year dog test a conditional requirement and necessary only on a case‐by‐case basis 25 . The rapid progress and advances in the sciences, agrochemical risk assessment and agricultural practice have made gradualism and incrementalism to develop internationally accepted testing and assessment methods ineffective.…”
Section: Optimizing Agrochemical Safetymentioning
confidence: 99%
See 1 more Smart Citation